2019
DOI: 10.1021/acs.analchem.8b05733
|View full text |Cite
|
Sign up to set email alerts
|

Use of Water Proton NMR to Characterize Protein Aggregates: Gauging the Response and Sensitivity

Abstract: Water proton transverse relaxation rate R 2(1H2O) measurements by NMR stand out as a powerful noninvasive tool to detect protein aggregates, including subvisible particles in biopharmaceutical formulations. To understand the applicability of water proton NMR (wNMR), we studied the response and sensitivity of wNMR to the aggregates of a monoclonal antibody (mAb) within a wide size range at different aggregate levels, for three different physical stresses: freeze–thaw cycling, heating, and agitation. We compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Recent publications have highlighted the use of benchtop NMR analysis as a nondestructive tool to analyze both solid and liquid drug products. Benchtop NMR, which has a small footprint and is nondestructive, has been used to analyze contents of tablets, [78] aggregation in monoclonal antibody liquid product [79,80], and adjuvant fill levels for vaccines [81]. These systems have the potential to aid in biophysical characterization, lot release testing, and stability assessment of the drug product at the fill finish facility.…”
Section: Portable and Remote Access Analyticsmentioning
confidence: 99%
“…Recent publications have highlighted the use of benchtop NMR analysis as a nondestructive tool to analyze both solid and liquid drug products. Benchtop NMR, which has a small footprint and is nondestructive, has been used to analyze contents of tablets, [78] aggregation in monoclonal antibody liquid product [79,80], and adjuvant fill levels for vaccines [81]. These systems have the potential to aid in biophysical characterization, lot release testing, and stability assessment of the drug product at the fill finish facility.…”
Section: Portable and Remote Access Analyticsmentioning
confidence: 99%
“…In the case of rather large aggregates, R 2 ( 1 H 2 O) might respond to their formation even at relatively low total protein concentrations, e.g., <0.5 mg/ml (Taraban et al, ). In general, R 2 ( 1 H 2 O) is most reliably sensitive to protein aggregate content >1% (Taraban, DePaz, et al., ).…”
Section: Strategic Planningmentioning
confidence: 99%
“…One way is to vary the level of the stress used to induce aggregation: for example, heating a protein solution to 60°C for 15 min, 30 min, 60 min, and so on. The other is to fix the stress level (e.g., heating to 60°C for 60 min) and then mix the stressed stock solution with different fractions of the unstressed solution of the same protein concentration (Taraban, DePaz, et al., ). The content of protein aggregates in calibration solutions should be measured by SEC.…”
Section: Strategic Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Taraban et al have shown that thermally and mechanically produced aggregation of recombinant antibodies could be quantified using spin-spin relaxation times T 2 of water protons [16,21]. The earlier works examined a two-site model that explains the significant increase of water proton relaxation rates, 1/T 2 , due to the exchange with protein protons [14].…”
Section: Introductionmentioning
confidence: 99%